Sailors, Slaves, and Immigrants Bondage in the Indian Ocean World, 1750–1914 - Stanziani, A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Slaves, convicts, and unfree immigrants have traveled the oceans throughout human history, but the conventional Atlantic World historical paradigm has narrowed our understanding of modernity. This provocative study contrasts the Atlantic conflation of freedom and the sea with the complex relationships in the Indian Ocean in the long 19th century.
Keywords: Imperialism; Asia—History.; World history; Social history; Imperialism and Colonialism; Asian History; World History, Global and Transnational History; Social History; History of South Asia